Anesthetic care for a child with undiagnosed myopathic/mitochondrial disease for gastrostomy tube placement and muscle biopsy. - D. M. Munlemvo; A. Syed; N. Kimmet; S. Hayes; J. D. Tobias (Pediatric Anesthesia and Critical Care Journal, 2020)
Disorders of the motor nerves, neuromuscular junction or muscle can affect children of all ages. These patients may present for therapeutic or diagnostic procedures (muscle and nerve biopsy) prior to arrival at a definitive diagnosis. The perioperative care of these patients is im- pacted by end-organ effects of the neuromyopathic con- dition including skeletal muscle weakness with its impact on upper airway control and respiratory function and my- ocardial involvement with arrhythmias, conduction dis- turbances or depressed function. Additionally, specific conditions may impact the choice of anesthetic care including choice of neuromuscular blocking agent, ma- lignant hyperthermia risk, and impact of propofol on mi- tochondrial function. We present a 12-month girl who presented with hypotonia, failure to thrive and biochem- ical evidence of a metabolic disorder with an elevated lactate and ammonia suggestive of a primary myopathic condition or a mitochondrial myopathy. Anesthetic care was required for a laparoscopic gastrostomy tube place- ment and muscle biopsy. The perioperative management of these patients is discussed with specific emphasis on implications of a primary myopathic or mitochondrial process.